Strategi Pembelajaran PAKEM - Hasta, Muharrida; Rama, Bahaking; Usman, Syahruddin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Learning is a teaching and learning process that involves teachers and students to develop intellectually, emotionally, morally, and others. The relationship between teachers and students is very important in successful learning. The PAKEM strategy (Active, Creative, Effective and Fun Learning) is used to explore and develop student potential with more active learning methods. The purpose of writing this paper is to understand the meaning, characteristics, characteristics, and advantages and disadvantages of PAKEM learning. The PAKEM method allows teachers to convey material in a varied way so that students can apply it innovatively and not boringly.